2019
DOI: 10.1016/j.jhazmat.2018.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of the aromatic fraction from petroleum diesel fuel by Oerskovia sp. followed by comprehensive GC×GC-TOF MS

Abstract: Highlights  PAHs degradation from diesel fuel aromatic fraction was investigated  Novel method was applied for the visualization degraded compounds in the GC×GC-TOF MS chromatograms  Oerskovia sp. CHP-ZH25 has successfully degraded different PAHs from diesel fuel aromatic fraction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…X5 degraded dinitrotoluene sulfonates and other nitroaromatic contaminants such as 2, 4, 6-trinitrotoluene, dinitrotoluene, and mononitrotoluene. Lješević et al (2019) demonstrated that Oerskovia sp. CHPZH25 isolated from petroleum oil-contaminated soils could degrade PAHs.…”
Section: Soil Bioremediationmentioning
confidence: 99%
“…X5 degraded dinitrotoluene sulfonates and other nitroaromatic contaminants such as 2, 4, 6-trinitrotoluene, dinitrotoluene, and mononitrotoluene. Lješević et al (2019) demonstrated that Oerskovia sp. CHPZH25 isolated from petroleum oil-contaminated soils could degrade PAHs.…”
Section: Soil Bioremediationmentioning
confidence: 99%
“…Since 2D gas chromatography (2D GC) provides mass sensitivity, simple sample preparation, and easy identification of compounds, it was a method of our choice. The 2D GC–MS has found application in the analysis of lignin degradation products [7], fuel biodegradation [8], food [9,10], and essential oil [11] analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2D gas chromatography (2D GC) provides mass sensitivity, simple sample preparation, and easy identification of compounds, it was a method of our choice. The 2D GC-MS has found application in the analysis of lignin degradation products [7], fuel biodegradation [8], food [9,10], and essential oil [11] analysis. The aim of this research was the screening of semi-VOCs in wheat and pea using 2D GC-MS to investigate their qualitative changes after their treatment with 200 mg L −1 uncoated (CeO 2 ) and glucose-, levan-, and pullulancoated nCeO 2 (glucose-coated cerium oxide nanoparticles (G-CeO 2 ), levan-coated cerium oxide nanoparticles (L-CeO 2 ), and pullulan-coated cerium oxide nanoparticles (P-CeO 2 )) during three weeks-growth in hydroponics.…”
Section: Introductionmentioning
confidence: 99%
“…The use of GC × GC for environmental analysis is expected to be especially effective for simultaneous analysis of compounds with multiple isomers and analogs, such as hydroxylated polychlorinated biphenyls (HO-PCBs) (Hashimoto et al, 2010;Rezek et al, 2012) and chlorinated paraffins (Eljarrat and Barcelo, 2006;Muscalu et al, 2017), which pose environmental risks but are difficult to measure. We have been developing methods using GC × GC / ToFMS (Fushimi et al, 2012;Hashimoto et al, 2008Hashimoto et al, , 2011Ieda et al, 2019;Lješević et al, 2019;Ochiai et al, 2011) and software tools to analyze the data generated (Hashimoto et al, 2013;Zushi et al, 2013Zushi et al, , 2014Zushi et al, , 2015Zushi et al, , 2017Zushi and Hashimoto, 2018) for environmental investigations.…”
Section: Introductionmentioning
confidence: 99%